2017
DOI: 10.1186/s12913-017-2672-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of hospitalizations and utilization of emergency outpatient services for ambulatory care sensitive conditions between asylum-seeking children and children of the general population: a cross-sectional medical records study (2015)

Abstract: BackgroundHospitalizations for ambulatory care sensitive (ACS) conditions are established indicators for the availability and quality of ambulatory care. We aimed to assess the differences between asylum-seeking children and children of the general population in a German city with respect to (i) the prevalence of ACS hospitalizations, and (ii) the utilization of emergency outpatient services for ACS conditions.MethodsUsing anonymous account data, all children admitted to the University Hospital Heidelberg in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
4
31
5
Order By: Relevance
“…Interestingly, in our study the asylum-seeking children had a lower proportion of emergency department visits compared to nonasylum-seeking children. This nding contrasts to a recently published study, showing that asylumseeking children were 5 times more likely to use emergency services [16]. One explanation for the lower proportion in our setting may be that the nurse-led health care system present at Swiss asylum-seeking reception centers which may help to prevent visits to the emergency department, as diseases are detected early.…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, in our study the asylum-seeking children had a lower proportion of emergency department visits compared to nonasylum-seeking children. This nding contrasts to a recently published study, showing that asylumseeking children were 5 times more likely to use emergency services [16]. One explanation for the lower proportion in our setting may be that the nurse-led health care system present at Swiss asylum-seeking reception centers which may help to prevent visits to the emergency department, as diseases are detected early.…”
Section: Discussioncontrasting
confidence: 96%
“…Current health care delivery models to asylum-seekers vary substantially between regions and countries. As mentioned in a German study, presentations with ambulatory care sensitive conditions at tertiary health care facilities could be used as an indicator to compare primary care delivery models for asylum-seekers in different regions (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct comparison between the groups was not done (15). Only one recent study from Germany included health care delivery data from both asylumseeking and non-asylum seeking children (16). The study showed that asylum-seeking children were more frequently admitted for diseases with the potential for outpatient care, when detected early In summary, there is a knowledge gap on recent health data of asylum-seeking children in comparison with non-asylum-seeking children.…”
mentioning
confidence: 99%
“…Mostly these have been developed on the basis of expert consensus procedures or by analysis of discharge records. ACS conditions for children were operationalised following an approach which we applied in a previous study 28. The approach synthesised seven international studies,21–27 which had identified and validated paediatric ACS conditions.…”
Section: Methodsmentioning
confidence: 99%